2018
DOI: 10.1051/e3sconf/20182801029
|View full text |Cite
|
Sign up to set email alerts
|

Use of metallurgical dust for removal chromium ions from aqueous solutions

Abstract: Abstract. The aim of the study was to determine the potential for the application of dust from steel plant as an effective sorbent for removing Cr(III) and Cr(VI) in the form of simple and complex ions -Acid Blue 193 dye from aqueous solutions. Three isotherms models were used to interpret the experimental results namely: Langmuir, Freundlich, and DubininRadushkevich. Estimated equations parameters allowed to determine the binding mechanism. Based on laboratory studies it was found that the dust was characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…With an increase in the initial concentration of Cr(III) from 0.1 to 10 mg L −1 , the pH of the equilibrium solution was constant, higher than that of the initial solution (maximum 5.8 for SO 2− 4 , pH 5.0), and then decreased to maximum 2.71 (Cl − , pH 3.0). The results indicated that the adsorption process may be accompanied by precipitation of chromium hydroxide Cr(OH) 3 for sulfate solutions at initial pH 5.0 and initial Cr concentration of 0.1-10 mg L −1 (Pieczara & Rzepa, 2016;Pajak et al, 2018). The presence of H + ions had significant influence on the adsorption capacity of the adsorbent at initial concentrations above 50 mg L −1 (Fig.…”
Section: Adsorption Of Cr(iii) Ions On Ferrihydritementioning
confidence: 89%
“…With an increase in the initial concentration of Cr(III) from 0.1 to 10 mg L −1 , the pH of the equilibrium solution was constant, higher than that of the initial solution (maximum 5.8 for SO 2− 4 , pH 5.0), and then decreased to maximum 2.71 (Cl − , pH 3.0). The results indicated that the adsorption process may be accompanied by precipitation of chromium hydroxide Cr(OH) 3 for sulfate solutions at initial pH 5.0 and initial Cr concentration of 0.1-10 mg L −1 (Pieczara & Rzepa, 2016;Pajak et al, 2018). The presence of H + ions had significant influence on the adsorption capacity of the adsorbent at initial concentrations above 50 mg L −1 (Fig.…”
Section: Adsorption Of Cr(iii) Ions On Ferrihydritementioning
confidence: 89%
“…Therefore, many studies propose using steel dust in applications where clays are similarly used. They are used as adsorbents to remove toxic and heavy metals from water [22][23][24][25][26][27][28], as catalyst [29][30][31], and for CO 2 sequestration [32,33]. In addition, steel dust was also reported to have been used for drill cuttings disposal [34,35].…”
Section: Introductionmentioning
confidence: 99%